Kreativitas Karyawan sebagai Variabel Mediasi antara Motivasi dan Kinerja Karyawan - Jean Jr., C.Venus Lurekke; Ferinia, Rolyana (www.bsi.ac.id, 2023)
The optimal performance of employees is the hope of every company; in fact, employee performance still needs to be improved. This condition can be caused by employees' lack of motivation and creativity. Therefore, this study aimed to determine the extent to which employee creativity acts as an intermediary variable for employee motivation and performance variables. This study uses a quantitative method and a correlational design. The data collection technique is to use a purposive sample. The instrument used was a questionnaire that was distributed through Google Forms. This research was conducted on 73 employees at PT. Global Solutions Science. The data analysis technique used in this study is Structural Equation Modeling (SEM), and analyzed using SmartPLS. The results of this study indicate that work motivation has a moderate effect on performance, work motivation has a substantial effect on employee creativity, employee creativity has a moderate effect on performance, and motivation has a moderate effect through employee creativity on performance. This study concludes that strengthening employee creativity must be balanced with employee motivation to achieve optimal performance. Keywords: Employee Creativity, Employee Performance, Motivation